STUB1 suppresseses tumorigenesis and chemoresistance through antagonizing YAP1 signaling - Tang, Dong‐E; Dai, Yong; Lin, Lie‐Wen; Xu, Yong; Liu, Dong‐Zhou; Hong, Xiao‐Ping; Jiang, Hao‐Wu; Xu, Song‐Hui (Cancer science, 2019)
Yes‐associated protein (YAP) is a component of the canonical Hippo signaling pathway that is known to play essential roles in modulating organ size, development, and tumorigenesis. Activation or upregulation of YAP1, which contributes to cancer cell survival and chemoresistance, has been verified in different types of human cancers. However, the molecular mechanism of YAP1 upregulation in cancer is still unclear. Here we report that the E3 ubiquitin ligase STUB1 ubiquitinates and destabilizes YAP1, thereby inhibiting cancer cell survival. Low levels of STUB1 expression were correlated with increased protein levels of YAP1 in human gastric cancer cell lines and patient samples. Moreover, we revealed that STUB1 ubiquitinates YAP1 at the K280 site by K48‐linked polyubiquitination, which in turn increases YAP1 turnover and promotes cellular chemosensitivity. Overall, our study establishes YAP1 ubiquitination and degradation mediated by the E3 ligase STUB1 as an important regulatory mechanism in gastric cancer, and provides a rationale for potential therapeutic interventions. Our study establishes YAP1 ubiquitination and degradation mediated by the E3 ligase STUB1 as an important regulatory mechanism in gastric cancer, and provides a rationale for potential therapeutic interventions.